BCSA Rawmix Design: Correlation between Chemical Constituents and Mineralogy - Suresh Palla; Suresh Vanguri; S Ramakrishna; S K Chaturvedi; B N Mohapatra (Universitas Gadjah Mada, 2021)
The cement industry has been identified as one of the main contributors to climate change due to greenhouse gas emissions, mainly CO2. Therefore, to meet CO2 reduction targets, cement producers are working on different strategies of minimizing its emission, one of which is alternative clinkers. This study assessed the impact of variations of the raw mix design, concerning the type and proportions of materials, on the formation of calcium sulphoaluminate belite-type clinkers. Various materials were used to produce raw mixes for different percentages of belite, yeeliminite, and other minerals in resultant clinkers. Computer-based theoretical mixes were designed with different percentages of SiO2, CaO, Al2O3, Fe2O3, and SO3 and then the designed mixes were fired in a laboratory furnace at 1250°C with 20 min retention time. The resultant clinker samples were characterized with X-ray diffraction. The quantification of minerals in each sample was carried out with Rietveld refinement. The obtained results confirmed the correlation between the mineralogy and chemical constituents in the raw mix. The C4AF percentage of the resultant clinker samples increased with an increase in Fe2O3 percentage. C4A3 content varied with the amounts of Al2O3, SO3, and CaO. The mineral percentage of C2S in the designed mixes had a clear correlation with the constituents of SiO2 and CaO. Anhydrite percentage in the resultant minerals changed with the SO3 content in the raw mix. These results should aid in the determination of the optimum amount of chemical constituents and minerals required for the development of calcium sulphoaluminate clinker.